Osseous genioplasty in conjunction with bimaxillary orthognathic surgery: a review of 262 consecutive cases. Issue 7 (July 2016) - Posnick, J.C.; Choi, E.; Chang, R.P.
Abstract: The purpose of this study was to evaluate the results of osseous genioplasty with bimaxillary orthognathic surgery. A retrospective consecutive case series of patients treated by a single surgeon between 2004 and 2013 was studied. All underwent Le Fort I, sagittal ramus osteotomies, septoplasty, inferior turbinate reduction, and osseous genioplasty. The outcome variables included the presenting chin dysmorphology, complications, and assessment of morphologic change. A Steiner analysis was completed for each subject's interval cephalogram. Two hundred sixty-two subjects met the inclusion criteria. Their mean age at operation was 25 (range 13–63) years. Chin osteotomy complications included one wound infection (0.4%), and two of the 1572 mandibular anterior teeth at risk sustained a pulpal injury. None of the subjects required revision. For subjects undergoing chin advancement, the mean change was +3.5 (range +3 to +6) mm. A majority also underwent counterclockwise rotation of the mandible (62%). For those undergoing chin lengthening, the mean change was +5 (range +3 to +12 mm) mm, and for those undergoing vertical shortening, the mean change was −3.5 (range −3 to −7) mm. Osseous genioplasty is confirmed to be a safe method to reshape the chin. When osseous genioplasty is performed in conjunction with bimaxillary orthognathic surgery, only a modest horizontal change is required to achieve the preferred pogonion projection.